Covalent coupling regulated thermal conductivity of poly(vinyl alcohol)/boron nitride composite film based on silane molecular structure. (October 2020) - Cheng, Hua; Zhao, Kai; Gong, Yi; Wang, Xiao; Wang, Rui; Wang, Fengyu; Hu, Rui; Wang, Fangkuo; Zhang, Xian; He, Jianying; Tian, Xingyou
Highlights: Thermal conductivity (TC) of poly(vinyl alcohol)/boron nitride composite film can be tuned by molecular structure of introduced silane coupling agents (SCAs). Length of the side chain of SCAs molecules suppresses the TC of composite film. Number of hydrolyzable Si-O-R of SCAs molecules affects the TC of composite through controlling the self-condensation degree of SCAs. Owing to the desired molecular structure, VTES improved TC of the composite film to 1.636 W/m·K, best among other investigated SCAs. Abstract: Creating covalent bonds between inorganic fillers and polymer matrix is an effective method to enhance the thermal conductivity (TC) of composite materials, while the detailed mechanism is still not clear. By introducing different silane coupling agents (SCAs) bonding poly(vinyl alcohol) (PVA) and functionalized boron nitride (fBN), intrinsic relationship between molecular structure of silane crosslinkers and TC of PVA-fBN composite has been systematically investigated. The results show that the SCAs molecules with short side chain, i.e. vinyl triethoxysilane (VTES) and tetraethyl orthosilicate (TEOS), increase the TC of composite polymer, with maximum value of 1.636 W/m·K, which is 337.3% of that of PVA/fBN. In contrast, 3-glycidoxypropyltrimethoxy silane (GPTMS) with long side chain decreases the TC to 54.4% of that of PVA-fBN. The number of hydrolyzable SiOR of SCAs molecules affects the TC of PVA-fBN composite through controlling the self-condensation degree of SCAs. Integrated with atomistic simulations, these findings provide new insights for the design of polymer-based thermal management materials.